Características mineralógicas e inclusiones fluidas de las esmeraldas del municipio de san antonio de yacopí, cundinamarca, colombia (1999)
The San Antonio de Yacopí emerald district is located in the western emerald belt of the Cordillera Oriental, in the Vásquez - Yacopí territory. The emerald mineralizations of this district are found in lower cretaceous marine sedimentary rocks belonging to the stratigrafical unit recognized as La Palma Group.  The emplacement characteristics of the mineralizations of the area suggest a tectonic control associated with regional and minor faults that are affecting the sedimentary sequence. The emeralds are found in veins, lenses and nodular deposits frequently associated with calcite veins, breccias, black shales and calcareous rocks.  The aim of this study is to extent the knowledge about the characteristics of the mineralizations and the analysis of the formation environment of the San Antonio de Yacopí emerald deposits. A mineralogical study was carried out, describing physical properties, such as refraction indexes of some emerald crystals and microthermometric properties of the fluid inclusion emerald crystals allowing the definition of thermobarometric conditions on the formation environment of the emerald deposits. Based on these studies it is possible to conclude that there are not remarkable differences in the cell parameters among the San Antonio, Coscuez, Muzo and Chivor emerald districts. The microthermometric data show that the temperatures of formation are in the range from 300°C to 350°C, being normal in the general context of the western emerald belt. The eutectic temperatures are low, indicating the presence of a complex mixture of dissolved ions in the aquous phase, including K+,Ca++,CI·, Fe+3, Mg++,AI+3.The thermobarometric measurements indicate a range of values from 900 to 1000 bars, suggesting that the emerald deposits were formed at shallow crust levels, at aproximately 800 m below the surface, closely associated with similar depths of formation assigned to other emerald localities including Muzo, Pacho, Coscuez and Chivor emerald districts. These deposits were formed from a unique mineralized fluid, being the small differences in composition attached to slightly local changes, related to local processes that were occurring at the moment of the emerald crystal formation.